2009
DOI: 10.1007/s10482-009-9389-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of gut microbiota increases with aging and starvation in the desert locust

Abstract: Here we report the effects of starvation and insect age on the diversity of gut microbiota of adult desert locusts, Schistocerca gregaria, using denaturing gradient gel electrophoretic (DGGE) analysis of bacterial 16S rRNA genes. Sequencing of excised DGGE bands revealed the presence of only one potentially novel uncultured member of the Gammaproteobacteria in the guts of fed, starved, young or old locusts. Most of the 16S rRNA gene sequences were closely related to known cultured bacterial species. DGGE profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 45 publications
3
61
2
Order By: Relevance
“…Indeed, the outside environment itself with different nectar and pollen sources and other less optimal conditions is very different from the constant rearing conditions indoors promoting a small and stable microbiota . In agreement, a shift in the gut bacterial diversity has been demonstrated in starving desert locusts Schistocerca gregaria compared to normal fed individuals (Dillon et al 2010). Although, a second hypothesis remains possible as our results indicated that most of the new OTUs, including Gamma-E3, have been linked with environmental sources (BLASTn results shown in Table I).…”
Section: Sobssupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, the outside environment itself with different nectar and pollen sources and other less optimal conditions is very different from the constant rearing conditions indoors promoting a small and stable microbiota . In agreement, a shift in the gut bacterial diversity has been demonstrated in starving desert locusts Schistocerca gregaria compared to normal fed individuals (Dillon et al 2010). Although, a second hypothesis remains possible as our results indicated that most of the new OTUs, including Gamma-E3, have been linked with environmental sources (BLASTn results shown in Table I).…”
Section: Sobssupporting
confidence: 87%
“…Core bacteria dominating the gut of social honeybees and bumblebees have been implicated in beneficial functions such as digestion and protection (Klungness and Peng 1984;Forsgren et al 2010;Vásquez et al 2012;Kwong et al 2014). Multiple conditions have been reported influencing the bacterial gut community, including the environment, host age, habitat, pathogens, and diet (Dillon et al 2010;Evans and Schwarz 2011;Hu et al 2014;Yun et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ten and 11 OTUs 0.03 clusters were observed in starved females and males, respectively, and might be caused by reduced gut peristalsis, which increased bacterial colonization [13,34]. Furthermore, some bacteria originally present in low abundance likely bloomed sufficient amounts to be detected by DGGE.…”
Section: Bacterial Community Structurementioning
confidence: 99%
“…Dillon and colleagues observed increased bacterial diversity in starved locusts, which might improve host defense against enteric threats due to the role of gut bacteria in colonization resistance [13]. Gut bacteria also have the potential to be used as a biological agent in pine forest protection.…”
Section: Introductionmentioning
confidence: 99%
“…Although most research has focused on food quality, several studies found that food quantity can affect the composition and functionality of the gut microbiota (Dillon et al, 2010;Freese & Schink, 2011). In mice, for example, starvation is known to alter the gut microbiota in a way that it confers health benefits to its host (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%